Damages and stress responses in sperm cells and other germplasms during dehydration and storage at nonfreezing temperatures for fertility preservation. Issue 12 (12th November 2022) - Comizzoli, Pierre; Amelkina, Olga; Lee, Pei‐Chih
Abstract: Long‐term preservation of sperm, oocytes, and gonadal tissues at ambient temperatures has the potential to lower the costs and simplify biobanking in human reproductive medicine, as well as for the management of animal populations. Over the past decades, different dehydration protocols and long‐term storage solutions at nonfreezing temperatures have been explored, mainly for mammalian sperm cells. Oocytes and gonadal tissues are more challenging to dehydrate so little to no progress have been made. Currently, the detrimental effects of the drying process itself are better characterized than the impact of long‐term storage at nonfreezing temperatures. While structural and functional properties of germ cells can be preserved after dehydration, a long list of damages and stresses in nuclei, organelles, and cytoplasmic membranes have been reported and sometimes mitigated. Characterizing those damages and better understanding the response of germ cells and tissues to the stress of dehydration is fundamental. It will contribute to the development of optimal protocols while proving the safety of alternative storage options for fertility preservation. The objective of this review is to (1) document the types of damages and stress responses, as well as their mitigation in cells dried with different techniques, and (2) propose new research directions.